Analogue spectra for impact ionization mass spectra of water ice grains obtained at different impact speeds in space - Klenner, Fabian; Postberg, Frank; Khawaja, Nozair A.; Reviol, René (Rapid communications in mass spectrometry, 2019)
Rationale Detecting ice grains with impact ionization mass spectrometers in space provides information about the compositions of ice grains and their sources. Depending on the impact speeds of the ice grains onto the metal target of a mass spectrometer, ionization conditions can vary substantially, resulting in changes to the appearance of the resulting mass spectra. Methods Here we accurately reproduce mass spectra of water ice grains, recorded with the Cosmic Dust Analyzer (CDA) on board the Cassini spacecraft at typical impact speeds ranging between 4 km/s to 21 km/s, with a laboratory analogue experiment. In this Laser-Induced Liquid Beam Ion Desorption (LILBID) approach, a μm-sized liquid water beam is irradiated with a pulsed infrared laser, desorbing charged analyte and solvent aggregates and isolated ions, which are subsequently analyzed in a time-of-flight (TOF) mass spectrometer. Results We show that our analogue experiment can reproduce impact ionization mass spectra of ice grains obtained over a wide range of impact speeds, aiding the quantitative analyses of mass spectra from space. Conclusions Spectra libraries created with the LILBID experiment will be a vital tool for inferring the composition of ice grains from mass spectra recorded by both past and future impact ionization mass spectrometers (e.g. the SUrface Dust Analyzer (SUDA) onboard NASA's Europa Clipper Mission or detectors on a future Enceladus Mission).
Gesehen am 12.12.2019